Purpose of life in family caregivers of people diagnosed with cancer - Huamani Cahua, Julio César (2017)
In this study we explore the purpose of life in 101 family caregivers of people diagnosed with cancer, selected by non-probabilistic sampled from Cancer Diseases Regional Institute at Arequipa. The sample was conformed by 58,4% female people and 41,6% male. The instrument used was Purpose in Life Test (Crumbaugh & Maholick, 1968), adapted for Noblejas (2000) in Latino sample. We found a purpose in life which indicates a clear existential aim in the 55,4% of the caregivers, without differences by age, type and cancer gravity. Although, there are significant diff erences by sex (p< 0.05), so the males have high er scores than women in perception of sense, goals and duties. Moreover, we observed that 9% of the caregivers have existential emptiness and absence of purpose in life, being the most of them, females.